Effect of CaF2 Substitution with TiO2 on the Crystallization Characteristics of Low-Fluoride Slag for Electroslag Remelting - Ju, Jiantao; Jialiang, An; Guangheng, Ji (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The effect of CaF2 substitution with TiO2 on the crystallization characteristics of low-fluoride slag for electroslag remelting were studied using differential scanning calorimetry (DSC) combined with XRD and SEM-EDS analysis. The effective activation energy for crystallization of the slag was calculated based on DSC thermal data. The results showed that the liquidus temperature of the slag increased unnoticeably with increasing TiO2 content. Increasing TiO2 addition from 4.3 wt% to 13.0 wt% decreased the undercooling of slag and enhanced the crystallization ability of the slag. There is no change in the type and precipitation sequence of the crystalline phase in the slag with different TiO2 contents during continuous cooling. The crystalline phases were Ca12Al14O32F2, CaTiO3, MgO and CaF2. The first and second crystallization phase were Ca12Al14O32F2 and CaTiO3, respectively. The dominant crystalline phase was faceted Ca12Al14O32F2 crystal. The morphology of CaTiO3 crystal changed from needle-like to blocky with increasing TiO2 content. The MgO crystal was with little blocky morphology, and the needle-like CaF2 distributed among CaTiO3 crystal. The precipitated amount of MgO and CaF2 were both very small. The effective activation energy for Ca12Al14O32F2 crystallization decreased with increasing TiO2 content in the slag, indicating that TiO2 enhanced the crystallization tendency of the slag.